Jurnal Jaringan Analisis dan pengembangan Virtual Local Area Network: Analisis dan pengembangan Virtual Local Area Network di Asy-Syarifiy Pandanwangi - Lumajang - Yulia Dwi Noviani (LPPM STMIK AMIK BANDUNG, 2020)
Along with the development of technology, especially computers and the internet, we can get information more easily. This also encourages the number of computer and internet users to grow. Especially in the SMK ASY-SYARIFIY IBS PANDANWANGI, the number of students and employees who use the internet is increasing from time to time. The increase in users using the network will cause the existing network infrastructure to be further improved so as not to disappoint users due to decreased network performance. VLAN is a technology that allows a LAN to be divided into several different domains. VLANs also allow the joining of networks that are separate locations, but seem to be located in the same domain. Research on the use of VLANs in the laboratory environment of SMK ASY-SYARIFY IBS PANDANWANGI provides results that VLAN is can improve network performance, share networks based on certain conditions, simplify management, minimize costs, and apply security methods.